2017
DOI: 10.1080/15384101.2016.1261225
|View full text |Cite
|
Sign up to set email alerts
|

Role for PADI6 in securing the mRNA-MSY2 complex to the oocyte cytoplasmic lattices

Abstract: The oocyte cytoplasmic lattices (CPLs) have long been predicted to function as a storage form for the maternal contribution of ribosomes to the early embryo. Our previous studies have demonstrated that ribosomal component S6 is stored in the oocyte CPLs and peptidylarginine deiminase 6 (PADI6) is critical for CPLs formation. Additionally, we found that depletion of PADI6 reduced de novo protein synthesis prior to the maternal-to-embryonic transition, therefore causing embryos to arrest at the 2-cell stage. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Consistent with western blotting, the MSY2 immunofluorescent signal decreased in Zar1/2 –/– oocytes; however, its cortical enrichment persisted. Collectively, these results suggest that ZAR1/2 may function together with MSY2 and CPL, which have been reported to be involved in maternal mRNA stabilization and mobilization in oocytes (46–47,49).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Consistent with western blotting, the MSY2 immunofluorescent signal decreased in Zar1/2 –/– oocytes; however, its cortical enrichment persisted. Collectively, these results suggest that ZAR1/2 may function together with MSY2 and CPL, which have been reported to be involved in maternal mRNA stabilization and mobilization in oocytes (46–47,49).…”
Section: Resultsmentioning
confidence: 56%
“…Therefore we further investigated the possible causes for the maternal transcriptome change. MSY2 is an RNA-binding protein that maintains global mRNA stability in mammalian germ cells (46,47). Zar1/2 knockout caused phenotypes resembling Msy2 knockout; female Msy2 –/– mice are infertile as their MII oocytes are severely compromised due to aberrant spindle formation and chromosome alignment (48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A), our results argue that L-bodies are distinct from stress granules, Pbodies, germ granules, and other cytoplasmic RNP granules such as RNase L Bodies (Burke et al, 2020), as more than a quarter (26.7%) of the identified L-body proteins are not found in these other RNP granule types. Proteins unique to L-bodies include a cytokeratin protein (Krt12), which could be involved in anchoring to the vegetal cortex, as cytokeratin proteins have been implicated in this process (Kloc et al, 2005), a Kinesin II subunit (Kif3a), which has been shown to play a role in vegetal RNA transport in Xenopus oocytes (Betley et al, 2004;Messitt et al, 2008), and a peptidyl arginine deiminase (Padi2), for which there is an oocyte-specific paralog (Padi6) in mouse (Liu et al, 2017). Our results also indicate that L-bodies are distinct from Xenopus germ granules, or Balbiani bodies.…”
Section: Discussionmentioning
confidence: 99%
“…This lattice is composed of fibrillary structures including intermediate filaments and other filamentous structures. It has been proposed that these structures function in the storage of ribosomes (Liu et al, 2017). Several genetic studies indicate that disruption of these structures leads to impaired developmental competence and defective embryo development.…”
Section: Oocyte Cytoplasmic Maturationmentioning
confidence: 99%